2018
DOI: 10.1101/387332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor Cortex Excitability Reflects the Subjective Value of Reward and Mediates its Effects on Incentive Motivated Performance

Abstract: 1Performance-based incentives tend to increase an individual's motivation, 2 resulting in enhancements in behavioral output. While much work has focused on 3 understanding how the brain's reward circuitry influences incentive motivated 4 performance, fewer studies have investigated how such reward representations act on 5 the motor system. Here we measured motor cortical excitability with transcranial magnetic 6 stimulation (TMS) while female and male human participants performed a motoric 7 incentive motivati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…While the spinal stretch reflex is extremely fast, it is difficult to assume an effect of reward or motivation occurring at the spinal level. On the other hand, transcortical feedback includes primary motor cortex processing (Pruszynski et al, 2011), a structure that shows sensitivity to reward (Bundt et al, 2016;Galaro et al, 2019;Thabit et al, 2011). Consequently, an exciting possibility for future research is that transcortical feedback gain is directly enhanced by the presence of reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the spinal stretch reflex is extremely fast, it is difficult to assume an effect of reward or motivation occurring at the spinal level. On the other hand, transcortical feedback includes primary motor cortex processing (Pruszynski et al, 2011), a structure that shows sensitivity to reward (Bundt et al, 2016;Galaro et al, 2019;Thabit et al, 2011). Consequently, an exciting possibility for future research is that transcortical feedback gain is directly enhanced by the presence of reward.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in saccades, reward reduces reaction times and sensitivity to distractors (Manohar et al, 2015). Reports also indicate that reward invigorates movement execution by increasing peak velocity and accuracy during saccades (Takikawa et al, 2002) and reaching movements (Carroll et al, 2019;Galaro et al, 2019;Summerside et al, 2018). Together, these studies suggest that reward can shift the speed-accuracy function, at least in isolation, of both selection and execution.…”
Section: Introductionmentioning
confidence: 91%
“…The premotor area is central to movement planning and several studies have shown its sensitivity to reward (Ramkumar et al 2016;Olson 2003, 2004). Regarding M1, a large literature demonstrates effects of reward on various aspects of M1 processing (Bundt et al 2016;Galaro et al 2019;Kapogiannis et al 2008;Mawase et al 2016Mawase et al , 2017Ramkumar et al 2016;Thabit et al 2011), making it a suitable candidate for mediating the reward-driven effects observed in our study. Furthermore, we show in Codol et al (2020) that some execution improvements may be due to an increase in feedback control, likely transcortical (Omrani et al 2016;Pruszynski et al 2011) and visuomotor feedback (Carroll et al 2019).…”
Section: Discussionmentioning
confidence: 89%
“…However, this would not explain previous reports of reward-driven increase in feedback control (Carroll et al 2019;Manohar et al 2019) and end-point stiffness (Codol et al 2020) during reaching tasks. Rather, reward could directly modulate M1, as M1 activity has been shown to be highly sensitive to reward (Bundt et al 2016;Galaro et al 2019;Kapogiannis et al 2008;Mawase et al 2016Mawase et al , 2017Ramkumar et al 2016;Thabit et al 2011;Zhao et al 2018), shaping processing near the end of the sensorimotor arc. Another reasonable hypothesis is that reward information is integrated earlier on, with M1 being merely the final recipient.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, late responses might also reflect motor preparation process that might reduce lick latencies. Human behavioral and EEG studies reported that reward affects this process ( Mir et al, 2011 ; Schevernels et al, 2014 ), which might be mediated through the basal ganglia including the ventral striatum ( Pasquereau et al, 2007 ; Galaro et al, 2019 ). The PVT might affect lick latency through its projections to the nucleus accumbens (see below).…”
Section: Discussionmentioning
confidence: 99%